Kolaborasi untuk Keunggulan: Menilik Strategi dan Capaian Kerja Sama Universitas Nusa Cendana - Djaha, Syukur Muhaymin Adang; Djaha, Ajis Salim Adang; Lily, Asnat Kristin (IAI Nasional Laa Roiba Bogor, 2025)
Collaboration between universities is a key strategy to enhance institutional capacity, educational quality, and graduate competitiveness. Universitas Nusa Cendana (UNDANA), the largest public university in East Nusa Tenggara, has established various partnerships at the university, faculty, and study program levels during the 2019–2023 period. However, partnership achievements indicate disparities among units and a lack of follow-up on agreements. This study aims to analyze UNDANA’s partnership performance, identify supporting and inhibiting factors, and provide recommendations to improve partnership effectiveness. A qualitative approach with an instrumental case study design was employed. Data were collected through open-ended interviews, document analysis, and observations, then analyzed using Creswell’s stages, with validation conducted through source, technique, and time triangulation. The findings reveal that the Faculty of Teacher Training and Education (FKIP) demonstrates the highest partnership performance, supported by clear standard operating procedures, adequate funding, and dedicated human resources for partnership management. The Faculty of Science and Engineering (FST) is in the medium category, while the Faculty of Social and Political Sciences (FISIP) ranks lowest due to limited internal support and strategic networking. Overall, UNDANA’s partnerships have developed significantly, yet six categories of partners remain untapped. Strengthening institutional capacity, leveraging strategic networks, and enhancing follow-up on agreements are essential to generate sustainable benefits.